Measurements of propagation velocity of ultrasonic wave at a frequency of 10 MHz in pure and deuterated KDP single crystals - DELEKTA, Olga; OPILSKI, Aleksander (Archives of Acoustics, 1980)
The results of determination of all elastic constants of a KH_2PO_4 single crystal (KDP), and in the case of KD_{2x}H_{2(1-x)}PO_4 crystals (DKDP) of constants C_{66} i C_{11} and the temperature dependence of the constant C66 at a frequency of 10 MHz are reported.The measurements showed an effect of deuteration on the constant C_{11} and on the change of the temperature dependence of C_{66} in the phase transition region.